Economic Valuation of Climate Change Induced Biodiversity Impacts on Agriculture : Results from a Macroeconomic Application to the Mediterranean Basin - Palatnik, Ruslana Rachel; Dias Nunes, Paulo Augusto Lourenço (Taylor and Francis, 2014)
It is clear that climate change involves changes in temperature and precipitation and, therefore, directly affects land productivity. However, this is not the only channel for climatic change to affect agro-systems. Biodiversity is also subject to climatic change. The present paper illustrates a unique attempt to economically assess the potential effects of climate change induced impacts of biodiversity on the agricultural sector in terms of changes in land productivity, changes in agricultural output and, ultimately, changes in national GDPs. Economic valuation shows that climate change induced impacts on biodiversity cause significant changes in GDP. However, the intensity of these changes varies across the economies under consideration. Some countries, and respective economies, show to be less resilient than others and, most of the time, the welfare changes involved clearly signal the presence of winners and losers. For example, the majority of non-EU Mediterranean economies are subject to a negative impact in their national GDP due to climate change-induced impacts on biodiversity that will be hampering the negative effect of climatic conditions on agro-ecosystems. These results reiterate the importance of welfare analyses of climate change-caused impacts on biodiversity that focus on the redistributive aspects involved with these impacts.